Development of Learning Evaluation Tools - Romli Burhani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The test in Indonesian has the meaning of a test, while in educational psychology the test is used to explain the instrument developed to measure and see and find test takers who can meet certain criteria. learning system that has been done. In the implementation of learning evaluation, of course, must use every aspect that drives the success of the activity. One very important aspect in evaluation activities is the development of learning evaluation tools. So on this occasion the author tries to discuss in depth about the development of evaluation tools. The methods used in this research are qualitative methods and library research. And the results obtained in this research indicate that there are several things that are considered important as an evaluation tool in implementing learning development.